(untitled) (Journal of Economic Research & Business Administration, 2017)
The purpose of this paper is to show the process of development of the real estate policy in the Republic of Kazakhstan, identified weaknesses of the approved state program. The stages of formation and methodological support for a housing policy are shown. The structure of housing stock is analyzed. The solution of the housing problem for many years remained one of the key tasks of the state policy of Kazakhstan. Accommodation in a market economy is the most representative indicator of growth, reflecting the dynamics of the various sectors of the economy, and public confidence in the future, the country as a whole. In this regard, the level of housing development is related to one of the most important characteristics of the socio-economic development. The article analysis the current state of the housing sector in Kazakhstan, the research offering methodological realization of state policies as new instrument in housing sector.